Lateral hypothalamic Orexin‐A‐ergic projections to the arcuate nucleus modulate gastric function in vivo. Issue 6 (7th November 2017) - Luan, Xiao; Sun, Xiangrong; Guo, Feifei; Zhang, Di; Wang, Cheng; Ma, Li; Xu, Luo
Abstract: It has been well‐known that hypothalamic orexigenic neuropeptides, orexin‐A, and melanin‐concentrating hormone (MCH), play important roles in regulation of gastric function. However, what neural pathway mediated by the two neuropeptides affects the gastric function remains unknown. In this study, by way of nucleic stimulation and extracellular recording of single unit electrophysiological properties, we found that electrically stimulating the lateral hypothalamic area (LH) or microinjection of orexin‐A into the arcuate nucleus (ARC) excited most gastric distension‐responsive neurons in the nuclei and enhanced the gastric function including motility, emptying, and acid secretion of conscious rats. The results indicated that LH‐ARC orexin‐A‐ergic projections may exist and the orexin‐A in the ARC affected afferent and efferent signal transmission between ARC and stomach. As expected, combination of retrograde tracing and immunohistochemistry showed that some orexin‐A‐ergic neurons projected from the LH to the ARC. In addition, microinjection of MCH and its receptor antagonist PMC‐3881‐PI into the ARC affected the role of orexin‐A in the ARC, indicating a possible involvement of the MCH pathway in the orexin‐A role. Our findings suggest that there was an orexin‐A‐ergic pathway between LH and ARC which participated in transmitting information between the central nuclei and the gastrointestinal tract and in regulating the gastric function of rats. Abstract : This study aimed to reveal whether and how the hypothalamic orexin‐A and melanin‐concentrating hormone (MCH) participated in the regulation of gastric function. We found that orexin‐A, when microinjected into the arcuate nucleus (ARC), regulated the gastric distension (GD)‐responsive neurons and enhanced gastric motility, which were partly blocked by SB334867 or PMC‐3881‐PI, antagonists for orexin‐A receptor and MCH receptor, respectively. The latter indicated that MCH pathway was likely involved in the process. Electrical stimulation of the lateral hypothalamic area (LH) increased the firing activities of GD‐responsive neurons in the ARC and promoted the gastric motility. When fluorogold was injected to the ARC, orexin‐A/fluorogold double‐labeled neurons were identified in the LH, indicating that HL‐ARC orexin‐A‐ergic projections existed, orexin‐A in the LH played a pivotal role in the central regulation of gastric motility and the ARC participated in the regulatory process of LH.